Commonwealth agriculture : a review of production, trade, and prices compiled in the Intelligence Branch of the Commonwealth Economic Committee - Commonwealth Economic Committee (London : Commonwealth Economic Committee, 1964)
The publication brings up to date much of the information given in the Committee's 35th report. A review of Commonwealth agriculture, production, and trade (1952) and in the previous memorandum Commonwealth agriculture (1955)
lje 28/06/2017
Loans
Keywords: Agriculture -- Economic aspects; Agriculture -- Economic aspects -- Colonies; Produce trade; Agricultural prices; Agriculture; Commonwealth countries; Great Britain